THE IMPLEMENTATION OF RATIONAL EMOTIVE BEHAVIOR THERAPY COUNSELING APPROACH THROUGH THOUGHT STOPPING TECHNIQUE AS AN ALTERNATIVE SOLUTION TO PERFECTIONISM - Khilman Rofi Azmi; Siti Liana Nurun Nisa (UIN Kiai Haji Achmad Siddiq Jember, 2022)
The development of Indonesian education can now be said to be more advanced. This is a positive thing. However, the competitiveness among students themselves in achieving good grades is increasing. Children who are above average usually have a sense of dissatisfaction with their learning outcomes if they are not in accordance with their ideals. And in this case, there is a high school student who experiences neurotic perfectionism, which wants to always be perfect so that if it is not achieved, negative things will occur. Things as a challenge in healing. So, the researcher tries to apply the Rational Emotive Behavior Therapy (REBT) approach because of the negative thoughts that arise, this approach is appropriate. And the technique used is Thought Stopping.